2019
DOI: 10.1021/acs.nanolett.8b04576
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Ultraviolet and High-Energy Visible Dielectric Metamaterials

Abstract: Photonic materials with tuneable and switchable ultraviolet (UV) to high-energy-visible (HEV) optical properties would benefit applications in sensing, high-density optical memory, beam-steering, adaptive optics and light modulation. Here, for the first time, we demonstrate a non-volatile switchable dielectric metamaterial operating in the UV-HEV spectral range. Nano-grating metamaterials in a layered composite of low-loss ZnS/SiO2 and the chalcogenide phase-change medium germanium antimony telluride (Ge2Sb2Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…Nevertheless, the integration of graphene layer with large area device can be hard due to its complex nanofabrication processes. In addition, the efficient THG were demonstrated using silicon photonic crystals and silicon metasurfaces …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the integration of graphene layer with large area device can be hard due to its complex nanofabrication processes. In addition, the efficient THG were demonstrated using silicon photonic crystals and silicon metasurfaces …”
Section: Introductionmentioning
confidence: 99%
“…When the GST is tuned between two states, the corresponding permittivity will be changed simultaneously, which can be used to realize active control. Due to its remarkable tuning abilities such as high stability and fast switch speed [29,30], GST has been applied in many novel tunable nano-photonic devices such as multi-wavelength duplex metalens, dipole-quadrupole (DQ) Fano resonance (FR) induced lateral force, beam steering, filter, color control, and ultraviolet/high-energy-visible resonances by combining with metasurfaces [20,[31][32][33][34][35][36], which has proved to be the great potential of GST. Nevertheless, the research for tunable metalens array using phase change materials has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from ©2016, American Chemical Society. d UV light-tunable meta-atom made of GST sandwiched by ZnS/SiO 2 layers [76]. Reproduced with permission from ©2019, American Chemical Society overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Gholipour et al demonstrated an optically-tunable metasurface, based on a patterned GST heterostrutcture with ZnS/SiO2 (Fig. 5d), showing tuning capability for ultraviolet (UV) and visible spectra [76]. GST shows a significantly low refractive index at the UV spectrum, as low as 1.07 at 245 nm in the crystalline phase.…”
Section: Thermally Tunable Metasurfaces Based On Phase Change Materialsmentioning
confidence: 99%